SWIMMING TRAINING USING FINS AS A METHOD OF DEVELOPING PHYSICAL FITNESS OF STUDENTS STUDYING IN PREPARATORY EDUCATIONAL INSTITUTIONS OF THE MINISTRY OF DEFENSE OF THE RUSSIAN FEDERATION - Antonov A.V.; Prokhorenko A.A.; Kolesnikov N.V.; Striga S.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to experimentally confirm the effectiveness of a specialized set of exercises for swimming with fins. This complex is aimed at improving the physical fitness of students studying in pre-university educational institutions under the jurisdiction of the Ministry of Defense of the Russian Federation. Methods and structure of the study. To solve the problems, the following research methods were used: theoretical analysis and generalization of literary sources, survey, pedagogical observation, pedagogical experiment. Results and conclusions. The analysis of the results showed that the average values ​​of the exercises performed in the experimental group exceeded the similar indicators of the control group. Consequently, there is a positive trend in improving the strength and speed-strength characteristics of the experimental group participants, which indicates the effectiveness of the applied set of exercises in swimming training with the inclusion of finswimming elements. The conclusions made confirm the rationality of using elements of underwater swimming in practical classes on physical training of cadets within the framework of the discipline "Swimming". This is considered as an additional way to improve overall physical fitness, increase the level of development of speed, endurance, strength and coordination, as well as the formation of moral, ethical and volitional qualities necessary for the development of a sporting character in students in pre-university educational institutions of the Ministry of Defense of the Russian Federation.